(untitled) (Academia Science Repository, 2023)
The problems of creating favorable socio-pedagogical conditions for the disclosure of the leadership potential of the individual are considered. The substantiation of the topic of scientific research of the educational space in which the formation of a socially significant orientation of the young leader and the development of his personal inclinations is given.